Government influence on energy prices - Klaus Matthies (Intereconomics, 1983)
There is now widespread agreement that, in the interest of energy conservation and substitution of oil, consumer prices for energy should reflect world market prices while taking account of longer-term trends. Are the energy policies of the major industrialised countries in conformity with this demand?
Keywords: 330